Soil Phosphorus Concentration under the Canopy of Perennial Grasses of Different Successional Stages Exposed to Water Stress - Busso, Carlos Alberto; Bolletta, Andrea Ivana (Taylor and Francis, 2022)
In this field study, the effects of water‐stress, rainfed, or irrigated conditions on soil phosphorus (P) concentration under the canopy of the native grasses of semi‐arid Argentina (late seral Stipa clarazii Ball., early serals S. tenuis Phil., and S. gynerioides Wild. Ex Steud) at different developmental stages and sampling dates during 1996 and 1997 were determined. Plants grew in a uniform matrix such that each plant of S. clarazii and S. tenuis was surrounded by four plants of S. gynerioides. In September 1996, Bray and Kurtz extracted soil P concentrations were greater under plants of S. clarazii if water stress was imposed during the vegetative stage than under rainfed conditions. Bray and Kurtz extracted soil P concentrations were either similar or between 8.7 to 31% greater under plants of S. clarazii than under those of the other two species. The higher nutrient concentration under S. clarazii than under S. gynerioides and S. tenuis may explain previously measured increases in density, frequency, and cover throughout a long‐term span (years) in the late over the earlier seral perennial grasses under field exclosures to domestic livestock or appropriate grazing management conditions.